Total ankle arthroplasty with TARIC prosthesis in the Unified Health System: The first 12 months of clinical and radiographic outcomes - Pereira Costa, Airton; de Souza Nery, Caio Augusto; Souza Maciel, Eduardo; Medina Moline, Matheus Giovanni; Cavazana Takata, Vanessa; Kerber Cavalcanti Lemos, André Vitor (Journal of the Foot & Ankle, 2026)
Introduction: The evidence of total ankle arthroplasty (TAA) in the Unified Health System (SUS) is limited. The objective was to describe early clinical and radiographic outcomes after primary TAA with TARIC (mobile-bearing) prosthesis in a public hospital. Methods: Retrospective case series (single center, single surgeon). Preoperative evaluation and at 3, 6, and 12 months by VAS, AOFAS, MOXFQ, and ROM; weight-bearing radiographs (AP/mortise/profile) with MDTA, STA, and talar tilt (references: MDTA 85°-95°, STA 80°-90°, tilt -2° to +2°). Paired endpoint: 12 months (n = 12); analysis by Wilcoxon. Results: At 12 months, there was a significant improvement in pain and function: VAS 8.33 ± 1.56→3.17 ± 2.66 (Δ 5.17 ± 2.62; p = 0.00049); AOFAS 40.67 ± 14.90→73.17 ± 14.89 (Δ 32.50 ± 14.96; p = 0.00049); total MOXFQ 0.80 ± 0.13→0.47 ± 0.24 (Δ 0.33 ± 0.25; p = 0.00049); ROM 20.25 ± 10.86→30.50 ± 7.54 (Δ 10.25 ± 16.52; p = 0.042). Radiographically, MDTA normalized (out: 16.7%→0%); STA improved (33.3%→16.7%) with two new cases outside the normal range; tilt talar was the most variable parameter (41.7%→50.0%). Implant-related events included indication for revision for polyethylene dislocation with replacement of the talar and poly components, talar subluxation, and severe varus tilt with polyethylene subluxation, and revision for INBONE at six months for severe arthrofibrosis and joint pain (< 12 months). Conclusion: TAA with TARIC in SUS showed early clinical improvement and consistent correction of the tibial axis; variability in talar tilt and revision events reinforce the need for reliable technical training, as well as systematic radiographic and long term follow-up.